2018
DOI: 10.1080/07448481.2018.1462816
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a sleep hygiene text message intervention on sleep in college students

Abstract: Self-efficacy for sleep hygiene is a modifiable factor that may serve to improve sleep quality. Sleep quality improved in both groups. Text messaging is a feasible approach to delivering an intervention to promote healthy behaviors among young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 36 publications
1
23
0
Order By: Relevance
“…Furthermore, time management was most related to sleep quality and significantly related to both sleep hygiene and knowledge. In this study, stress was found to impact quality of sleep, sleep hygiene, and time management (Gipson et al, 2019). Overall, sleep quality improved for both the control group and intervention group while the hours of sleep decreased from the baseline posttest.…”
Section: In the Article "Associations Between Sleep And Lifestyle Bementioning
confidence: 65%
See 3 more Smart Citations
“…Furthermore, time management was most related to sleep quality and significantly related to both sleep hygiene and knowledge. In this study, stress was found to impact quality of sleep, sleep hygiene, and time management (Gipson et al, 2019). Overall, sleep quality improved for both the control group and intervention group while the hours of sleep decreased from the baseline posttest.…”
Section: In the Article "Associations Between Sleep And Lifestyle Bementioning
confidence: 65%
“…Therefore, the hypothesis was not supported. It was found that time management improved in those in the sleep intervention group and not in the attention control group (Gipson et al, 2019). However, the sleep intervention group showed an improvement in the disruptive subscale score while it remained the same for the attention control group.…”
Section: In the Article "Associations Between Sleep And Lifestyle Bementioning
confidence: 82%
See 2 more Smart Citations
“…This is consistent with prior studies that found that erratic and unhygienic sleep practices result in sleep deprivation and daytime sleepiness. [ 38 ]…”
Section: Discussionmentioning
confidence: 99%